2020
DOI: 10.1002/lio2.453
|View full text |Cite
|
Sign up to set email alerts
|

“No drain, no gain”: Validation of novel quinsy simulation model

Abstract: Objectives To test a novel, low‐cost, home‐made model for needle aspiration of PTA. To ascertain whether simulation‐based teaching using this model was superior to lecture‐based teaching in increasing confidence and reducing anxiety relating to PTA aspiration. To assess whether there was an improvement in outcomes for PTA patients at one hospital following the delivery of a simulation‐based training session using our model. Methods We designed two teaching sessions for junior doctors starting work in ENT: a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…1). Ten articles were included in the final review, five from the US, 11,12,[19][20][21] three from the UK, [22][23][24] and two from Canada. 25,26 Two studies trained participants on both needle aspiration and I&D, 11,19 four studies on I&D only, 12,21,25,26 and four on needle aspiration only.…”
Section: Demographics and Tasks (Fig 1 And Table Ii)mentioning
confidence: 99%
See 3 more Smart Citations
“…1). Ten articles were included in the final review, five from the US, 11,12,[19][20][21] three from the UK, [22][23][24] and two from Canada. 25,26 Two studies trained participants on both needle aspiration and I&D, 11,19 four studies on I&D only, 12,21,25,26 and four on needle aspiration only.…”
Section: Demographics and Tasks (Fig 1 And Table Ii)mentioning
confidence: 99%
“…25,26 Two studies trained participants on both needle aspiration and I&D, 11,19 four studies on I&D only, 12,21,25,26 and four on needle aspiration only. 20,[22][23][24] Of the four needle aspiration studies, one utilized ultrasound guidance during the procedure (Table II). 20 The proportion of junior residents with minimal previous exposure to PTA (≤5 procedures) was indicated in 3 studies and was found to range from 87.5% to 100%.…”
Section: Demographics and Tasks (Fig 1 And Table Ii)mentioning
confidence: 99%
See 2 more Smart Citations
“…Eight simulators were identified for general otolaryngologic emergent procedures and sleep surgery (Supplemental Table 4). [67][68][69][70][71][72][73][74] Three of these models used adult sized intubation trainers, such as the Laerdal SimMan, to simulate airway foreign body removal, endoscopic diverticulotomy, and laser safety in the operating room. Notably, the endoscopic diverticulotomy model involved inserting a cut surgical glove posteriorly into the esophagus of the SimMan to simulate Zenker's diverticulum.…”
Section: General/sleepmentioning
confidence: 99%